LOCAL CULTURE REPRESENTATION IN THE TEXTBOOK ENGLISH FOR CHANGE OF THE MERDEKA CURRICULUM: A CRITICAL DISCOURSE ANALYSIS STUDY - Laoli, Adieli; Gulo, Ferna ceriah; Gea, Dwi elfi notalenta; Zebua, Muharni sartika; Mendrofa, Nurshyiam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to analyze the representation of local culture in the textbook English for Change. This study employs a qualitative approach using content analysis. The data were collected from texts, dialogues, and images found in the textbook. The findings indicate that local culture is represented through daily life themes, traditions, social values, and Indonesian social contexts, although the proportion remains lower than that of foreign cultures. These findings are expected to contribute to textbook development by encouraging a better balance between local and global cultural content.